Sensory properties of iodine-biofortified potatoes - Piochi, Maria; Chiavaro, Emma; Cichelli, Angelo; Torri, Luisa; Cerretani, Lorenzo (Italian Journal of Food Science, 2021)
The present study assessed the sensory impact of potatoes biofortification with iodine and the stability of iodine during six months of storage. Four biofortified cultivars (Cupido, Marabel, Orchestra and Universa) and their controls (non-biofortified) were evaluated. Descriptive analysis was applied with a panel to describe the sensory properties, and triangle tests were applied with consumers to evaluate perceivable differences between controls and respective biofortified samples at the end of shelf life. Iodine content was quantified on raw potatoes for three periods of storage. Descriptive analysis showed some differences between controls and iodine-biofortified samples, especially in texture (hardness). However, consumers did not significantly discriminate fortified from unfortified samples. Iodine was stable during storage in all varieties. Orchestra cultivar showed the highest iodine content, while Universa the lowest.